Hybrid wireless mesh network - Hossain, Foez Md Iqbal; Imran, Misbah Uddin Md.; Ahmed, Md. Saleh (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2013.